Gambaran Tingkat Pengetahuan Terhadap Perilaku Hygiene Sanitasi Makanan Pada Tenaga Pengolahan Makanan Di Rumah Makan Taman Sari - Santosa, Airi Yanti Putri; , Rusdin Rauf, S.TP., M.P; , Dwi Sarbini, S.ST., M.Kes (2016)
Introduction: Cultivating good food that is cooking a meal based on the principles of food hygiene and sanitation which includes knowledge, attitudes, and behavior of food processors in obeying the principles of health, hygiene principles, the principle of security in handling food to produce healthy and safe food for consumption. Objective: To describe the level of knowledge of the behavior of food sanitation hygiene in food processing power at Rumah Makan Taman Sari Methods: This study is an observational study using cross sectional data analysis techniques used in this study were univariate. Results: The study was conducted on 28 respondents, respondents overall female sex as much as 28 (100%), the majority of respondents aged 25-30 years with 16 (57.1%), long working respondents mostly one year as many as nine (32.1 %), and the last education is high school respondents largely as much as 15 (53.6%). The level of knowledge in both categories as many as 18 (64.3%), the level of knowledge with categories quite as much as 8 (28.6%) and the level of knowledge respondents with less category 2 (7.1%). The level of the behavior of respondents with good category were 19 (67.9%) and the behavior of respondents with category level is not good as much as 9 (32.1%). The level of knowledge both have good behavior. Conclusion: The level of knowledge of management of the food at Restaurant Taman Sari mostly either category. Sanitation Hygiene behavior in serving food at food processing power at Restaurant Taman Sari mostly either category. Keywords : Knowledge, Behavior, Sanitation Hygiene